The first Afrotropical species of Porophila Dybas (Coleoptera, Ptiliidae) - Jałoszyński, Paweł (Zootaxa, 2020)
Porophila Dybas was so far represented by four nominal species distributed in USA (Oregon) and the Russian Far East (Primorsky Krai). The first Afrotropical species, P. chakalaka sp. n. is described, based on specimens collected in the western region of Republic of South Africa. The new species is associated with fruiting bodies of the Polyporaceae fungus Lenzites elegans (Spreng.) Pat. (= Trametes elegans (Spreng.) Fr.). Morphological structures of P. chakalaka are illustrated in detail, and host fungus associations of Porophila species are summarized.